A BREATH CLOSE TO DEATH: A CASE REPORT OF IDIOSYNCRATIC REACTION TO WELDING FUMES - Saeed, Tamar; Bashir, Jawad; Hameed, Fawad (Journal of Ayub Medical College Abbottabad, 2019)
A 39-year-old gentleman presented to emergency department with a few hours’ history of acute shortness of breath, cough and haemoptysis that developed whilst welding a steel tank in a closed container. He was welder by profession for thirteen years with no significant past medical history. The arterial blood gas showed severe oxygenation impairment and he was intubated for mechanical ventilation. The radiographs showed bilateral widespread interstitial shadowing. The echocardiography showed normal heart and ruled out cardiogenic pulmonary oedemic. The microbiological investigations were all normal. He was treated as Acute Respiratory Distress Syndrome (ARDS) secondary to exposure to welding metal fumes in a closed container. He was given limited tidal volume invasive ventilation, extubated successfully after twelve days, transferred to respiratory ward for rehabilitation and discharged few days later. Exposure to welding metal fumes at work place is a major occupational health hazard worldwide. It can cause ARDS and other respiratory illnesses such as bronchitis, metal fumes fever and chronic pneumonitis. The pathogenesis of ARDS due to welding metal fumes involves direct inhalational injury and/or immune system dysfunction. Welding metal fumes related ARDS remains the diagnosis of exclusion and all other causes must be ruled out. The key to treatment is ventilation support with early endotracheal intubation. Appropriate precautionary measures are advised to avoid occupational health hazards in welding profession. Keywords: Emergency; ARDS; Haemoptysis; Welding; Bronchitis